Gerakan Islah di Tunisia pada Abad ke-19: Islah Movement in Tunisia in 19th Century - Kamis, Zaid Husaini; Mohd Nor, Mohd Roslan; Ali @ Mat Zin, Aizan (Journal Al-Muqaddimah, 2024)
The purpose of this research is to examine Islah Movement in Tunisia. Islah according to Kamus Dewan Bahasa is to return certain situation to a right condition, precise and suitable and to solve contention with good manner and peaceful path. Therefore, Islah Movement in Tunisia refer to purification of Tunisia from calamity and damage toward a better country that moved by Khairuddin at-Tunisi, Tahir Ibn ‘Ashur dan others. Islah Movement give good affect towards Tunisia society until French protectorate happened in the year of 1881. This research make use of documentation method to collect qualitative data. Data analised using method of comparative, inductive and deductive. Research finding showed that the effort of Islah give benefit to Tunisia in the aspect of economy, education, military and administration. Islah movement also gives vast benefit in the aspect of thinking and knowledge in the muslim world.